PENGGUNAAN ELEKTRODA BESI (Fe), TEMBAGA (Cu) DAN STAINLESS STELL PADA PROSES ELEKTROKOAGULASI LIMBAH SAUS SAMBAL UNTUK MENURUNKAN PARAMETER BOD DAN TSS - Purwati, Dewi; -, Alimuddin; -, Erwin (JURNAL ATOMIK, 2018)
Research on the decline in BOD and TSS from waste chili sauce with electrocoagulation method using electrodes Fe, Cu and stainless stell in decreased amount of BOD and TSS. Conducted to determine the optimum point of each parameter based on the reaction of the electrocoagulation process on waste samples of chili sauce by using a variation of time and variation of voltage. The results obtained show that the effect of time is obtained optimum time of 120 minutes with vigorous optimum voltage of 12 volts to the decreased amount of BOD and TSS, respectively for 10.7577 mg/L and 18 mg/L with the results of successive allowance for 99.17% and 98.36% for electrode Fe and stainless stell. And decreased amount of BOD and TSS respectively for 8.2482 mg/L and 296 mg/L with the preliminary results of a row of 99.36% and 73.09% for the electrode Fe and Cu. With initial values of BOD and TSS each of 1301.4010 mg/L and 1100 mg/L.